Sustainable Ecology Scale: Development Study for Secondary School Students - Arslan, Kevser; Görgülü Arı, Aslı; Akçay, Behiye (Universitas Pendidikan Indonesia, 2025)
This study aimed to develop a valid and reliable Sustainable Ecology Scale for secondary school students. The exploratory sequential design, a type of design within mixed-methods research, was employed. The study sample consisted of 500 secondary school students from various grade levels. To construct the draft version of the scale, a 96-item question pool was generated based on predefined learning objectives. In the initial phase, the draft scale was reviewed by expert evaluators, resulting in a reduction to 69 items. Following a pilot study, necessary adjustments were made, and the final version was implemented in the main study. The collected data were analyzed using statistical software, and both exploratory factor analysis and confirmatory factor analysis were conducted to ensure construct validity. The scale’s reliability was assessed through Cronbach’s alpha internal consistency coefficient, while item analyses, item-total correlation values, and factor correlations were examined. The results of CFA confirmed a three-factor structure, with fit indices indicating an acceptable to excellent model fit. As a result, a five-point Likert-type Sustainable Ecology Scale consisting of 32 items was developed, demonstrating a high internal consistency (Cronbach's alpha = 0.934). The findings indicate that the developed scale is a valid and reliable measurement tool suitable for assessing sustainable ecology awareness among secondary school students.